2016
DOI: 10.1126/science.aad2156
|View full text |Cite
|
Sign up to set email alerts
|

Mouse oocytes differentiate through organelle enrichment from sister cyst germ cells

Abstract: Oocytes differentiate in diverse species by receiving organelles and cytoplasm from sister germ cells while joined in germline cysts or syncytia. Mouse primordial germ cells form germline cysts, but the role of cysts in oogenesis is unknown. We find that mouse germ cells receive organelles from neighboring cyst cells and build a Balbiani body to become oocytes, whereas nurselike germ cells die. Organelle movement, Balbiani body formation, and oocyte fate determination are selectively blocked by low levels of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
326
1
14

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(356 citation statements)
references
References 20 publications
15
326
1
14
Order By: Relevance
“…The efficacy of multiple processes, including primordial germ cell migration, oogonial proliferation, nurse-cell organelle transfer and oogonial incorporation into primordial follicles, all contribute to the initial primordial follicle count (Kerr et al 2013, Lei & Spradling 2016. Subsequent primordial follicle activation, programmed cell death and oocyte extrusion from the ovary are processes that further affect the size of the ovarian reserve at puberty (Wordinger et al 1990, Tingen et al 2009).…”
Section: Amh In the Context Of Ovarian Reserve At Pubertymentioning
confidence: 99%
“…The efficacy of multiple processes, including primordial germ cell migration, oogonial proliferation, nurse-cell organelle transfer and oogonial incorporation into primordial follicles, all contribute to the initial primordial follicle count (Kerr et al 2013, Lei & Spradling 2016. Subsequent primordial follicle activation, programmed cell death and oocyte extrusion from the ovary are processes that further affect the size of the ovarian reserve at puberty (Wordinger et al 1990, Tingen et al 2009).…”
Section: Amh In the Context Of Ovarian Reserve At Pubertymentioning
confidence: 99%
“…Using 17.5 dpc ovaries, organ culture studies indicated that KITL enhances germ cell cyst breakdown and oogonia growth (Jones & Pepling 2013). Although molecular mechanism underlying germ cell attrition is unknown, a recent murine study indicated that dominant oogonia receive cytoplasm, mitochondria, microtubules and centrosome from neighboring oogonia via intercellular bridges and gaps (Lei & Spradling 2016). Neighboring germ cells are connected to each other via a channel protein, TEX14 (Greenbaum et al 2009).…”
Section: Germ Cell Attrition and Continuing Developmentmentioning
confidence: 99%
“…This similarity in timing suggested that the temperature-sensitive period for the mito-nuclear incompatibility may coincide with events of early oogenesis in the germarium. Indeed, early oogenesis is a crucial time for mitochondrial dynamics when germline mitochondria undergo a period of rapid proliferation and increase greatly in number, with some mitochondria actively transported into the differentiating oocyte to form part of a distinct cluster called the Balbiani body (Cox and Spradling, 2003;Hill et al, 2014;Lei and Spradling, 2016;Pepling, 2016;Pepling et al, 2007). To address whether these processes were affected, we labeled mitochondria with antibodies against ATP5a, a subunit of the F1 ATP synthase complex, and examined them by confocal and super-resolution microscopy (Godbout et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…In fly strains that are heteroplasmic for different mtDNA haplotypes, the events of early oogenesis are associated with selection and inheritance of functional mitochondria (Ma et al, 2014). Similar mitochondrial proliferation, transport and selection also occur during mouse oogenesis, and defects in these processes can negatively impact oogenesis and embryonic survival in both fly and mouse (Cox and Spradling, 2003;Lei and Spradling, 2016;Mishra and Chan, 2014;Pepling, 2016;Van Blerkom, 2011).…”
Section: A275vmentioning
confidence: 99%